Nutmeg Oil as an Anesthetic for Enhanced Gas Diffusion in High-Density Seabass Seedlings - Cut Laura, Cut Laura; Wahab, Gunawan Abdul; Putra, Dedi Fazriansyah; Al-Fairusy, Muhajir (Universitas Islam Negeri Ar-Raniry, 2026)
Asian seabass (Lates calcarifer) is a high-value aquaculture species cultivated to supply domestic and export markets. However, water quality deterioration during transport—marked by declining dissolved oxygen (DO) and rising carbon dioxide (CO₂) levels due to increased fish respiration and limited gas diffusion governed by Henry's Law—can induce stress and reduce seed survival. This study aimed to evaluate the effect of nutmeg oil (Myristica fragrans Houtt.) as an anesthetic on the survival and physiological response of Asian seabass seeds transported at different stocking densities, and to determine the optimal density for wet closed-system transportation. The experiment, conducted in February 2025 at the Faculty of Marine and Fisheries, Syiah Kuala University, employed a completely randomized design with five treatments and four replications. Treatments included a control (without anesthetic) and nutmeg oil administration (1.0 ppm) at densities of 25, 35, 45, and 55 fish. Transportation lasted for eight hours. Nutmeg oil significantly affected anesthesia induction and recovery time (P<0.05) but had no significant effect on survival (P>0.05). The highest survival rate (98.88%) was observed at 45 fish per container with 1.0 ppm nutmeg oil. The findings suggest nutmeg oil is an effective natural anesthetic for improving transport efficiency and fish welfare, supporting SDG 14 (Life Below Water) through sustainable aquaculture practices.